2005
DOI: 10.22358/jafs/67140/2005
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolites and haematological indices of pregnant beef cows fed rumen-protected methionine

Abstract: The effect of rumen-protected DL-methionine on some blood biochemical and haematological values of cows in approximately the last 102 days of pregnancy was examined. Twenty-six cows in the third stage of gestation were divided into two groups of equal number, a control (C) and an experimental group (E). Cows were fed meadow hay, maize grain silage and a 500 g fodder mixture (35% CP). In addition to the fodder mixture, cows in group E received 15 g rumen-protected DLmethionine per animal daily (Mepron ® M85). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Since the diet containing protected methionine did not affect body weight gain it can be assumed that methionine was not the limiting amino acid. No evident changes were found in metabolic and haematological indicators which would support the findings of a deficiency of methionine in group C, which was found to be possible in late pregnancy (Liker et al, 2005). Potentially, the protein source of protein-rich concentrates may have provided an adequate concentration of methionine in the duodenum without the need for amino acid supplementation.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Since the diet containing protected methionine did not affect body weight gain it can be assumed that methionine was not the limiting amino acid. No evident changes were found in metabolic and haematological indicators which would support the findings of a deficiency of methionine in group C, which was found to be possible in late pregnancy (Liker et al, 2005). Potentially, the protein source of protein-rich concentrates may have provided an adequate concentration of methionine in the duodenum without the need for amino acid supplementation.…”
Section: Resultsmentioning
confidence: 51%
“…Infusion of methionine, lysine and leucine to Angora goats decreased plasma cortisol concentrations (P<0.05) (Puchala et al, 1995). A deficit of methionine in beef cows in late pregnancy can cause the reaction manifested as increased secretion of glucocorticoids (Liker et al, 2005).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…No significant differences were observed in serum ALT and AST activity of female blue foxes among methioninesupplemented groups (P>0.05) with different doses (2, 4, 6, and 8 g/kg) for 40 days (Guo et al, 2015). In this respect, Liker et al (2006) stated that when Charolais growing beef cattle (average BW:249.6±43.8kg) received 10 g of rumenprotected DL-methionine daily for 94 days, plasma urea concentration tended to decrease at the end of the trial. The activity of ALT in these animals increased on the 68 th and 94 th days.…”
Section: Kidney and Liver Functionsmentioning
confidence: 78%
“…Some grazing experiments with cattle have shown positive responses of the growth of steer to the dietary addition of RPM (Gomez et al 2011), whereas other studies have shown no effect (Liker et al 2006) at doses of 10 g/day. The reason that the intermediate dose decreased weight gain in this experiment is unclear, but the possibility that deer respond to higher doses than those used in this experiment should not be excluded.…”
Section: Discussionmentioning
confidence: 99%